A Good community school program is based on sound human relations (Education Quarterly, 1958)
This study proved the assumption that in any community school human relations program the key persons are the leaders holds true and is valid in Torres-Bugallon, which is a model rural community school in the country. The fact that it is almost a unanimous opinion of those interviewed to the effect that the present success leadership, and in this particular case, democratic leadership which in turn has developed lay leadership, is the key factor in the promotion of sound human relations.